Expanding access to HIV testing and counseling and exploring vulnerabilities among spouses of HIV-positive men who inject drugs in Pakistan. Issue 1 (March 2016) - Shahid, Salman; Majeed, Mohammad Faisal; Awaan, Ahmad Bakhsh; Mirza, Humayun; Sarfraz, Nasir; Veronese, Vanessa
Abstract : Objectives: To explore the utility of home and community-based HIV testing and counseling (HTC) to increase detection of undiagnosed HIV among female spouses and children of HIV-positive PWID in Punjab province, Pakistan. Design: Between March 2014 and March 2015, home-based HTC was provided by a local NGO to spouses of HIV-positive PWID in Lahore, Faisalabad, and Sargodha. Convenience sampling was used to identify 2400 married, HIV-positive men who inject drugs and who were currently registered and receiving harm reduction services from the NGO 'Roshan Rasta ' and seek consent to approach their wives. Method: Trained outreach teams conducted HTC and administered a short sociodemographic and behavioral questionnaire to consenting spouses in their homes. HIV-exposed children were also tested with parental consent. Results: of the 2400 married HIV positive male-injecting drug users, only 1959 spouses were approached and 1896 agreed to HTC (96.8%). HIV prevalence was 5.3% ( n  = 101) among spouses and they had very low level of HIV-related knowledge and protective behaviors Conclusion: Home and community-based HTC was effective in identifying undiagnosed HIV among spouses of PWID, the majority of whom reported low rates of prior HIV testing and low HIV-related knowledge. Expansion of HIV prevention services and linkages to treatment and care including PMTCT are urgently needed for this group.